Samoocena uravnavanja čustev in subjektivno blagostanje pri študentih razrednega pouka in socialne pedagogike - Smrtnik Vitulić, Helena; Prosen, Simona (Revija za elementarno izobraževanje, 2015)
Self-Assessed Emotion Regulation and WellBeing in Primary Education and Social Pedagogy Students. In the study, emotion regulation (ER) strategies according to Gross and Thompson’s model (2009) and well-being were analysed in students of primary education (n = 116) and of social pedagogy (n = 54). The most frequently students used situation selection and selection modification, physical activation, and social support seeking and the least frequently psychoactive substance use. Students of primary education use ER strategies of attentional deployment, physiological response modulation and social support seeking significantly more than students of social pedagogy. The students of primary education reported significantly higher levels of well-being than the students of social pedagogy.